Kepuasan Ibu Hamil atas Layanan Konseling Gizi di Wilayah Kerja Puskesmas Jatinangor - Kiki Sundari (Jurnal Kesehatan Vokasional, 2019)
Background: Malnutrition in pregnant women and infants has contributed to at least 3.5 million deaths every year. Counseling on the importance of fulfilling nutrition during pregnancy is very necessary to be carried out as a promotive and preventive effortby midwives services. Patient satisfaction is one indicator of the success of nutrition counseling sevices. Satisfaction is subjective and the result of an affective reactionby characteristics of mothers based on reproductive age, education, and occupation. Objective: This study aims to identify characteristics of mothers, satisfaction with nutrition counseling services provided by midwives in general and specifically based on five dimensions of satisfaction, and frequency of respondents' characteristics of satisfaction levels in general in the work area of the JatinangorPrimary Health Care.Methods: The research method used was descriptive from primary data with the number of respondents participated was 77 pregnant womentaken usingaccidental sampling, data analysis used was univariate.Results: The results of the study showed a majorityof pregnant women age 20–35 years (81.81%) with a satisfaction rate of 72,73%, senior high school graduates (48.05%) with a satisfaction level of 41.56%, and the majority do not work (83.12%) with a satisfaction rate of 71.43%.Conclusion: In general, 88,31% of mothers said they were satisfied, 48,05% mothers were satisfied on the dimensions of tangibles and 100% mothers were satisfied based on the four another dimensions of satisfaction.